Human coagulation factor Xa prevents oligomerization of anti-coagulant phospholipases A2. (11th December 2013) - Ostrowski, Maciej; Žnidaršič, Petra Prijatelj; Raynal, Bertrand; Saul, Frederick; Faure, Grazyna
Abstract: Anti-coagulant FXa-binding Viperidae snake venom phospholipases A2 (sPLA2 ) have been identified as specific, exogenous, non-competitive FXa-inhibitors. Detailed knowledge of the sites of interaction of PLA2 with FXa is essential for understanding the hemostatic process at the molecular level and is important for the development of new anti-coagulant drugs. New insight was obtained by structural and biophysical studies including detailed analysis of the CA-CB-binding interface of crotoxin determined by X-ray crystallography and comparison with the CB-FXa-binding interface determined by molecular docking simulations. In this short review we describe our investigations that contribute to a better understanding of the possible role of PLA2 oligomerisation in the anti-coagulant effect of PLA2 .